1996
DOI: 10.1097/00007890-199607270-00007
|View full text |Cite
|
Sign up to set email alerts
|

Noncompliance in Children and Adolescents After Renal Transplantation

Abstract: This study assesses the perceptions, knowledge, and attitudes of patients and parents attending the Pediatric Transplant Unit at the Johannesburg Hospital. Fifty-six children with renal transplants accompanied by their parents were assessed by means of a questionnaire. The children's ages were 2.53 to 20.85 years. Eleven of twelve in the noncompliant group were male and nine were Black. The ages of the two groups of patients and distance traveled to the transplant center were similar. The noncompliant group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 10 publications
2
70
3
Order By: Relevance
“…Consistent with other studies in the child and adolescent population, we found evidence of nonadherence in our subjects at both interviews (11)(12)(13)(14). Several studies have examined nonadherence with medications among children and adolescents and report widely varying rates, ranging from 18% to 69% (8)(9)(10)13,14,71). Although differences in methodologies employed to assess medication nonadherence makes meaningful comparisons difficult, our rates of 13.6% at each of the two interviews appear to be less than the lower end of this range.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with other studies in the child and adolescent population, we found evidence of nonadherence in our subjects at both interviews (11)(12)(13)(14). Several studies have examined nonadherence with medications among children and adolescents and report widely varying rates, ranging from 18% to 69% (8)(9)(10)13,14,71). Although differences in methodologies employed to assess medication nonadherence makes meaningful comparisons difficult, our rates of 13.6% at each of the two interviews appear to be less than the lower end of this range.…”
Section: Discussionsupporting
confidence: 90%
“…Although differences in methodologies employed to assess medication nonadherence makes meaningful comparisons difficult, our rates of 13.6% at each of the two interviews appear to be less than the lower end of this range. Only one study specifically examined missed clinic visits and found that 29% of the total sample of children and adolescents did not attend clinic regularly (10). In comparison, our rate of 50% at the first interview was higher, and 31.8% at the second interview was about the same.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Key risk factors include lower socioeconomic status, passive parent involvement, side-effects related to medications and poor communication with health care teams [27,[30][31][32][33][34].…”
Section: The Importance Of Transition Servicesmentioning
confidence: 99%
“…Additionally, the healthcare team monitors for side effects of medications, which can frequently lead to facial swelling, acne, and weight gain. Often, female adolescent transplant recipients cite cosmetic reasons for discontinuing their medication (Meyers, Thomson, & Weiland, 1996). Studies have suggested that children who received a vital organ transplant have more behavioural problems and less social competence than healthy peers (Uzar et al, 1992).…”
Section: Introduction To Paediatric Heart Transplantmentioning
confidence: 99%